Inhomogeneous mass flow rate measurement of solid particles using a single electrostatic sensor - Rahmat, Mohd. Fua'ad (IEEE, 2011)
The development of reliable, cost effective and high accuracy instrument to mass flow rate measurement is becoming increasingly important in many industries. Appropriate measurement method and design leads to improvement of pneumatic conveyors operation and process efficiency. This paper present an instrument design based on passive charge detection using a single electrostatic sensor. A time domain signal processing algorithm is developed to measurement of mass flow rate from acquired electrical charge signal. The findings is led to a low cost and high accuracy design, the experimental test results of the design shows less than ±5% error between measured mass flow rate and reference reading acquired from the manual weighing.